Social Engineering and Policy Innovation in the Rehabilitation of Drug Addicts: Legislative Insights from the Restorative Justice Model in Indonesia - Ngaisah, Siti; Widoyoko, Wredha Danang; Ismail, Ismail; Rahmawati, Diah Ayu; Haryono, Haryono (West Science Interdisciplinary Studies, 2024)
This study examines the integration of social engineering and policy innovation within Indonesia’s legislative framework for drug rehabilitation, focusing on restorative justice principles. Through a juridical analysis of Law No. 35 of 2009 on Narcotics and related policies, the research highlights the shift from punitive measures to rehabilitation-focused approaches. Findings reveal that while legislative provisions align with restorative justice ideals, significant gaps in implementation—such as inadequate rehabilitation infrastructure, social stigma, and weak stakeholder coordination—hinder their effectiveness. Drawing insights from international best practices, the study proposes actionable reforms, including enhanced judicial guidelines, public awareness campaigns, and integrated policy frameworks, to promote a comprehensive and sustainable approach to drug rehabilitation in Indonesia. This research underscores the potential of restorative justice as a transformative tool for addressing drug addiction as a public health and social issue.